Kepemimpinan Pendidikan Untuk Meningkatkan Daya Saing di Madrasah Aliyah Kampar Timur - Irawati Irawati; Mhd Subhan (Universitas Pesantren Tinggi Darul Ulum (Unipdu) Jombang, 2017)
Leadership is an attempt to influence others to participate in achieving educational goals. Education requires the headmaster's efforts to improve competitiveness and have a strategy to improve competitiveness. It is carried out by means of making a strategic plan of work in developing madrasah to improve competitiveness, good administration and giving authority and responsibility to educators in accordance with the prevailing rules, the application of teacher discipline, educational staff and students, improving the quality of human resources (teachers and educational personnel), increasing the motivation of educators and educational staff, establishing good relationships with local communities, involving local communities in madrasah activities and applying student-based management. This study aims: to formulate the definition of educational leadership; know the leadership of education at Madrasah Aliyah Kampar Timur; know the strategy of education leadership in Madrasah Aliyah Kampar Timur in an effort to improve competitiveness.